Antinociceptive Effect of the Essential Oil Obtained from the Leaves of Croton cordiifolius Baill. (Euphorbiaceae) in Mice. (2nd March 2015) - Nogueira, Lenise de Morais; da Silva, Monalisa Ribeiro; Santos, Simone Maria dos; de Albuquerque, Julianna Ferreira Cavalcanti; Ferraz, Igor Cavalcanti; Albuquerque, Thaíse Torres de; Mota, Carlos Renato França de Carvalho; Araújo, Renata Mendonça; Viana, Glauce Socorro de Barros; Martins, René Duarte; Havt, Alexandre; Ximenes, Rafael Matos
Abstract : Croton cordiifolius Baill. is a shrub known as "quebra-faca" and is used to treat inflammation, pain, wounds, and gastrointestinal disturbances in the semiarid region in the northeast of Brazil. In an ethnobotanical survey in the state of Pernambuco, "quebra-faca" use was cited in 33% of the interviews. Thus, we decided to evaluate the antinociceptive effects of the essential oil from C. cordiifolius (CcEO). Chemical analysis by gas chromatography-mass spectrometry revealed 1, 8-cineole (25.09%) and α -phellandrene (15.43%) as major constituents. Antinociceptive activity was evaluated using murine models of chemically induced pain (writhing induced by acetic acid, formalin, capsaicin, and glutamate tests). Opioid and central nervous systems (CNS) involvement were also investigated. Regarding antinociceptive activity, CcEO (50 and 100 mg/kg) reduced the number of writhing responses induced by acetic acid and decreased the licking times in both phases of the formalin test. CcEO also was evaluated in capsaicin- and glutamate-induced nociception. While no effect was observed in the capsaicin test, CcEO (100 mg/kg) was effective in the glutamate test. Naloxone, an opioid antagonist, did not affect the antinociceptive activity of CcEO in writhing test. In conclusion, the antinociceptive effect of CcEO could be explained, at least in part, by inhibition of the glutamatergic system.